Peranan Perusahaan Keagenan terhadap Pengoperasian Kapal Niaga: Studi Kasus - Mohammad Shohibul Anwar; Dedi Nuryaman (Dinamika Bahari, 2021)
Indonesia is called a maritime country because part of its territory is water. That way, Indonesia has the opportunity to become a maritime axis country in Asia and the world. This opportunity must be realized to its full potential, namely by maximizing activities at the port properly. Activities to facilitate shipping activities both loading and unloading, sea expeditions and so on are needed for the benefit of the agency's role. One of them is the role of the PT. Indo Dharma transportation located in Surabaya. This company has a role in the merchant ship wars in the Surabaya area. The purpose of this study is to describe the role of agency companies in the operation of commercial ships in the Surabaya area.This research is a qualitative research using observation, interview and documentation methods. Through this research, it was found that the case of PT. Indo Dharma Transport Surabaya Branch provides convenience and smooth operation of commercial vessels in the Surabaya Port area.